UPAYA MENINGKATKAN MINAT BELAJAR ANAK DENGAN METODE ACTIVE LEARNING - Bagus Mahardika (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2020)
The objectives of this classroom action research are (1) increasing children's interest in learning in Kindergarten Sulthoni, (2) Knowing how to use active learning methods to increase children's learning interest, (3) Knowing how children's perceptions and impressions of active learning methods in increasing children's learning interest . This research is a Classroom Action Research (PTK). The research subjects were students of group B TK Sulthoni. The data collection techniques used were observation, documentation and interviews. The results of the study concluded that active learning for treasure-seeking strategies can increase children's interest in learning, especially calistung learning in students in group B TK Sulthoni with an increase in cycle I 60%, cycle II 75%, cycle III to 90%, (2) The seriousness of students in the cycle I 45%, cycle II 60%, Cycle III to 75%, accuracy of sisawa in cycle I 25%, cycle II 50%, cycle III to 80%, (4) Ability to arrange words into sentences in cycle I 45%, cycle II 60%, cycle III becomes 80%. Keywords: Interest in Learning, Children and Active Learning